PENDAMPINGAN IBU HAMIL DALAM PENGGUNAAN APLIKASI SISTEM INFORMASI DETEKSI DINI RISIKO KEHAMILAN BERBASIS WEBSITE DI WILAYAH KELURAHAN MENANGGAL KOTA SURABAYA - Santi, Dwi Rukma; Yalina, Nita; Kusumawati, Estri; Kumalasari, Mei Lina Fitri (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2018)
Early warning information system of pregnancy risk can be used to pregnant women and health care provider detection.? Early warning information system of pregnancy risk is useful to assist the health care provider an effort to enhance objectiveness early conclusion/diagnosis obtained. In addition, this information is useful for pregnant women and families to detect early pregnancy and risk factors can also be used to prepare for childbirth and safe motherhood. The objective of this public service is introducing application of early warning information system of pregnancy risk based of web to the public (pregnant women) at Menanggal Village - City of Surabaya. The method with lectures, demonstrations and practical. Results achieved increased knowledge of pregnant women about application of early warning information system of pregnancy risk. Evaluation of pregnant women obtained that features the application? of interesting, easy to understand, easy to use and responsive to complaints of pregnant women because there is room on the menu consultation. Dissemination and use of such application must be sustainability.Key Word : Dissemination, Information System, Early Warning, Pregnancy Risk.